Zernûcî Ta‘lîm’inin Osmanlı’daki İlk Şârihi: Mir’âtü’t-Tâlibîn’in Yazarı Üsküplü Kılıççızâde midir? (4th International Balkan Studies Congress Proceedings, 2025)
Ta’līm al-Muta’allim written by Burhan al-Din Zarnuji (d. late VI/XII century), a Hanafi fiqh scholar, is considered one of the most important sour-ces in the history of Islamic education. Although it has been cited by various thinkers since the eighteenth century, it was undoubtedly the Ottoman madra-sas that propelled this work to its true fame. First with Abdülmecid b. Nasuh b. Israil’s (d. 887/1482) Irşad al-talibīn and then with Jaleb Mustafa al-Üsküdari’s Tercüme-i Ta’līm al-Muta’allim, the sharhs and hashiyas written by the Ottoman scholars on the work, which was brought into Turkish, formed a special litera-ture and Ta’līm gained the identity of a classical education book that is taught even today. Today’s researchers mostly refer to Ibn Ismail’s Sharh Ta’līm al-Mu-ta’allim and Ismail b. Osman Osmanpazari’s Tafhīm al-Muta’allim. The literary contributions of scholars such as Ibrahim b. Ali al-Karsi (Lu’luu’l al-mansūr) have not been investigated sufficiently even at the level of belonging. Moreover, the commentary written by Ibn Ismail (d. after 996/1587-88) in 996/1587-88 for the education of the princes of Sultan Murad III (d. 1003/1595) is considered to be the first commentary on Ta’līm al-muta’allim. The primary aim of this paper is to subject the Ta’līm al-muta’allim literature to a holistic analysis and To question the possibility that Mir’at at-Talibīn, registered in the name of Ishak b. Ibrahim, is the first commentary by Kılıççızade Ishak Çelebi. For this purpose, on the one hand, all commentaries that constitute the relevant literature will be classified in terms of references in bio-bibliographical sources and the copyright/intensi-ve records of manuscripts. On the other hand, in the context of its sources and in-text citations, the relationship of Mir’at at-talibīn with other Ta’lîm commen-taries and other works of Kılıççızade Ishak Çelebi will be analysed. Therefore, while making a new proposal regarding the chronological order of the commen-taries of Ta’līm al-muta’allim, the existence of a new work by Ishak Çelebi will also be opened to discussion.